Twist n’ Taste 2-in-1 bottle / Puteri Batrisya Mohamad Shahril … [et al.] - Mohamad Shahril, Puteri Batrisya; Ab. Hadi, Nurhaziera Hasni; Kamarulzaman, Nur Rabiatul Adawiyah; Badrul Hisham, Nurul Nabila; Kardi, Nurul Asmiera (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
The Twist n’ Taste 2-in-1 Bottle presents a novel solution to combat the pervasive issue of excessive sugar consumption by offering a convenient and healthier alternative to sugary drinks. This innovative product combines a foldable water bottle with flavored, foldable straws, promoting hydration on the go without compromising on taste or health. With a focus on addressing the pressing concerns of obesity and diabetes, particularly in Malaysia, this bottle aims to revolutionize beverage consumption habits and promote healthier lifestyles. Through its compact and portable design, infused with various natural flavors such as orange, blackcurrant, strawberry, and chocolate, the Twist n’ Taste 2-in-1 Bottle provides an enticing option for consumers to stay hydrated while minimizing their sugar intake.